2015
DOI: 10.1002/ccd.26004
|View full text |Cite
|
Sign up to set email alerts
|

Use of rotational angiography in assessing relationship of the airway to vasculature during cardiac catheterization

Abstract: 3DRA can visualize airway anatomy and its relationship to the vasculature accurately. This has significant implications for preinterventional planning, intraprocedural management, as well as postprocedural recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Our results compare well with the study from Aldoss et al, which reported a median DAP of 72.3 µGym 212 . Truong et al published similar low radiation doses (DAP = 85 µGym 2 ) 17 . Conversely, the study of Haddad et al showed a higher median DAP with 278.0 µGym 2 .…”
Section: Diagnostic Utility and Image Qualitymentioning
confidence: 84%
“…Our results compare well with the study from Aldoss et al, which reported a median DAP of 72.3 µGym 212 . Truong et al published similar low radiation doses (DAP = 85 µGym 2 ) 17 . Conversely, the study of Haddad et al showed a higher median DAP with 278.0 µGym 2 .…”
Section: Diagnostic Utility and Image Qualitymentioning
confidence: 84%
“…This is important for the interventionalist. Thomas Fagan: I started using systems for 3D guidance fairly early, mostly working with a specific company that started with not such simple equipment, and actually took quite a long time, especially with 3DRA, to reconstruct images and then be able to use those for overlay guidance [22,23,[25][26][27]29]. It was very cumbersome, time intensive, added a fair amount of time to procedures.…”
Section: Sebastian Gorecznymentioning
confidence: 99%
“…These structured interviews recorded during the 21 st Pediatric and Adult Interventional Cardiac Symposium (PICS, November 2018) illustrate the challenges and sticking points as well as giving an insight into the direction of travel for 3D imaging and fusion techniques. Covering a wide range of career development, seniority and experience, the interviewees in this article are probably responsible for the majority of the published literature on invasive 3D imaging in congenital heart disease [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. They each collaborate with a broad range of industry partners to map out the future direction of invasive imaging with specific reference to our complex patient group.…”
Section: Introductionmentioning
confidence: 99%
“…This rotational angiogram provides a robust data set, which can be post-processed into a 3D reconstruction within minutes. The source images obtained are identical to that of a cross-sectional CT scan, therefore in addition to post-processing into a 3D reconstruction, the cross-sectional CT images may also be viewed and are particularly useful for visualizing soft tissue structures, allowing for the operator to appreciate relationships and interactions between vascular/cardiac structures and other soft tissue structures within the chest (82,83).…”
Section: D Rotational Angiography (3dra)mentioning
confidence: 99%
“…However 3DRA can provide diagnostic quality images in the majority of cases with comparable overall radiation and contrast doses to standard cineangiography (84)(85)(86)(87). The 3D reconstructions are particularly useful in understanding complex pulmonary artery or aortic arch anatomy and the relation of these vascular structures to soft tissue structures such as the airway (82,83), frequently providing additional, clinically relevant data when compared with standard biplane angiography (87). While dependent in part on the structure being visualized, quantitative measurements of structures made by 3DRA are comparable to those by 2D angiography (88).…”
Section: D Rotational Angiography (3dra)mentioning
confidence: 99%